ANALYSIS OF MOTIVATION AND SERVICE MARKETING MIX FACTORS INFLUENCING THE CHOOSING OF HEALTH TOURISM SERVICES BY THAI TOURISTS : CASE STUDY OF CHAO PHYA ABHAIBHUBEJHR HOSPITAL, PRACHINBURI PROVINCE - Maneerat Sukkasem มณีรัตน์ สุขเกษม; Prasopchai Pasunon ประสพชัย พสุนนท์ (Dusit Thani College Journal, 2018)
The objectives of this research were to analyze the motivation of Thai tourists influencing the choosing of health tourism, a case study of Chao Phya Abhaibhubejhr Hospital, Prachinburi Province and to analyze the service marketing mix factors influencing the choosing of health tourism services of Thai tourists of Chao Phya Abhaibhubejhr Hospital, Prachinburi Province. The samples used in the study were 400 Thai tourists travelling to Chao Phya Abhaibhubejhr Hospital, Prachinburi Province. The data were collected through questionnaires during October 1-30, 2014. The questionnaire was developed based on the motivations and service marketing mix factors theories. The data were analyzed by frequency, percentage, mean, standard deviation. Finding was utilized the principal component analysis method and orthogonal rotation by Varimax method. The findings indicated that the motivation towards health tourism services included; 1) health promotion factor, 2) Thai identity factor and 3) repeat trends factor. The service marketing mix factor towards health tourism services to 7 factors are; 1) service factor, 2) environment factor, 3) promotional activities factor, 4) value for money factor, 5) image factor, 6) location factor, and 7) facilities factor.